Pengaruh Kompensasi Dan Motivasi Terhadap Prestasi Kerja Karyawan PT Kimia Farma Apotek Unit Bisnis Tasikmalaya - Isti Sindrika Ekawati; Arga Sutrisna; Depy Muhamad Pauzy (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
This study aims to determine the effect of compensation on employee performance at PT Kimia Farma Apotek Tasikmalaya Business Unit. The research method used is a quantitative descriptive method with a sample of 79 people. The data analysis tool used in this research is path analysis. The results of this study indicate that compensation has a positive and significant effect on work performance. Employee motivation has a positive and significant effect on work performance. Compensation has a positive and significant effect on employee motivation, compensation through motivation does not have a significant effect on employee performance. This means that motivation is not able to mediate compensation for employee performance.